Pengaruh Digital Marketing dan Kualitas Produk pada Keputusan Pembelian Melalui Brand Awareness - Muhammad Farhan; Yulasmi Yulasmi; Nila Pratiwi (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to examine how much influence digital marketing and product quality have on purchasing decisions with brand awareness as an intervening variable in consumers of Nanggalo Sudut Kopi, Pesisir Selatan. Data collection methods through surveys and circulating questionnaires, with a population of 9,000 consumers per year 2023 with a sample of 100 respondents obtained from Slovin. The analysis method used is Structutal Equation Modeling (SEM) using SmarttPLS. The research results obtained where there is an insignificant positive effect of Digital Marketing on Brand awareness. There is a significant positive effect of product quality on brand awareness. There is a positive and significant effect of digital marketing on Purchasing Decisions. There is a negative and insignificant effect of brand awareness on purchasing decisions. There is a positive and insignificant effect of product quality on purchasing decisions. There is a positive and insignificant effect of digital marketing on purchasing decisions through brand awareness. There is a positive and insignificant effect of product quality on purchasing decisions through brand awareness.